Dual role of ethyl bromodifluoroacetate in the formation of fluorine-containing heteroaromatic compounds. Issue 65 (22nd June 2018) - Ma, Xingxing; Mai, Shaoyu; Zhou, Yao; Cheng, Gui-Juan; Song, Qiuling
Abstract : An efficient one-pot cascade process via unprecedented quadruple cleavage of BrCF2 COOEt with primary amines to afford valuable fluorine-containing heterocycles is described, in which BrCF2 COOEt plays a dual role as a C1 synthon and a difluoroalkylating reagent for the first time. Abstract : An efficient one-pot cascade process via unprecedented quadruple cleavage of BrCF2 COOEt with primary amines to afford valuable fluorine-containing heterocycles is described, in which BrCF2 COOEt plays a dual role as a C1 synthon and a difluoroalkylating reagent for the first time. Mechanistic studies supported by DFT calculations suggest that a base plays an active role in the formation of the key intermediate isocyanides generated in situ from primary amines and difluorocarbene.